Miraj̱ā Sāhibāṃ de kisse - Aravindara Kaura,Pīlū (Wārisa Ṣ̣āha Fāūṇḍeṣana, 2016)
Study, with text, of a romantic tale Mirazā Sāhibāṃ by Pīlū, 16th century Panjabi poet
Includes bibliographical references (pages 111-112). - In Panjabi
Keywords: Pīlū active 16th century; Legends